Chemical Speciation of Trace Elements in Soil Fertilized with Biomass Combustion Ash and Their Accumulation in Winter Oilseed Rape Plants - Małgorzata Szostek; Ewa Szpunar-Krok; Anna Ilek (Agronomy, 2023)
The impact of fertilization of fly ashes from biomass combustion (BAs) on the changes in the chemical speciation of trace elements (Zn, Cu, Cr, Ni, Pb, Cd) in Gleyic Chernozem soil was analyzed in field-experiment conditions, under cultivation of winter oilseed rape plants. The three-year field experiment was carried out in southeastern Poland (50°3′ N, 22°47′ E). The three-stage sequential extraction procedure developed by the Measurements and Testing Program (BCR) was used for the fractionation of trace elements in BAs and soil. The risk assessment code (RAC) coefficient was used to assess potential soil contamination with trace elements from Bas. The total content of Zn, Cu, Cr, Ni, Pb, and Cd in BAs used in the experiment was 470, 311, 29, 78, 38, and 3.7 mg kg−1, respectively. The present study showed that the application of BAs significantly increased the total concentration of Zn and Cu in the surface layer of the Gleyic Chernozem soil, and did not significantly increase the concentration of Cr, Ni, Pb, and Cd. Generally, using BAs does not significantly change the chemical speciation of trace elements in soil. Regardless of the applied fertilization, residual fraction (F4) was the most abundant, whereas the exchangeable/extractable (F1) fraction and reducible (F2) fraction were present in the smallest amounts. Due to the low share of exchangeable/extractable fraction (F1), the BAs used in the experiment were characterized by a low RAC coefficient; hence, their use as a soil fertilizer is relatively safe for the environment. The BAs fertilization did not cause significant changes in the content of trace elements in the different parts of the winter oilseed rape plants. Due to the relatively high content of trace elements in fly ashes from biomass combustion, an analysis of the content of individual trace element fractions should be carried out to assess their actual impact on the environment. This can help indicate further actions that should be taken to limit their negative environmental impact.